Prediction of settlement of road construction on peat - Sutejo, Yulindasari (Faculty of Civil Engineering, 2008)

(untitled)
Construction over peat deposit is undesirable due to poor physical properties, low shear strength and bearing capacity as well as high compressibility. However, in some cases, the construction over peat is unavoidable. The major problem associated with such construction is the prediction of settlement because the conventional analysis usually under predicts the secondary compression or creep which continued for a long time. New approaches were proposed by researchers, but the application of the new method was limited. This paper discusses some approaches on the estimation of settlement of construction on peat based on the long term compressibility characteristics. Prediction of settlement by different approach was made for a hypothetical case of embankment on peat deposit. The results were compared with data obtained from settlement monitoring of road construction over peat soil.